Gabapentin Administration Reduces Reactive Gliosis and Neurodegeneration after Pilocarpine-Induced Status Epilepticus - Rossi, Alicia Raquel (2013)
The lithium-pilocarpine model of epilepsy reproduces in rodents several features of human temporal lobe epilepsy, by inducing an acute status epilepticus (SE) followed by a latency period. It has been proposed that the neuronal network reorganization that occurs during latency determines the subsequent appearance of spontaneous recurrent seizures. The aim of this study was to evaluate neuronal and glial responses during the latency period that follows SE. Given the potential role of astrocytes in the post-SE network reorganization, through the secretion of synaptogenic molecules such as thrombospondins, we also studied the effect of treatment with the α2δ1 thrombospondin receptor antagonist gabapentin. Adult male Wistar rats received 3 mEq/kg LiCl, and 20 h later 30 mg/kg pilocarpine. Once SE was achieved, seizures were stopped with 20 mg/kg diazepam. Animals then received 400 mg/kg/day gabapentin or saline for either 4 or 14 days.In vitro experiments were performed in dissociated mixed hippocampal cell culture exposed to glutamate, and subsequently treated with gabapentin or vehicle. During the latency period, the hippocampus and pyriform cortex of SE-animals presented a profuse reactive astrogliosis, with increased GFAP and nestin expression. Gliosis intensity was dependent on the Racine stage attained by the animals and peaked 15 days after SE. Microglia was also reactive after SE, and followed the same pattern. Neuronal degeneration was present in SE-animals, and also depended on the Racine stage and the SE duration. Polysialic-acid NCAM (PSA-NCAM) expression was increased in hippocampal CA-1 and dentate gyrus of SE-animals. Gabapentin treatment was able to reduce reactive gliosis, decrease neuronal loss and normalize PSA-NCAM staining in hippocampal CA-1. In vitro, gabapentin treatment partially prevented the dendritic loss and reactive gliosis caused by glutamate excitotoxicity. Our results show that gabapentin treatment during the latency period after SE protects neurons and normalizes PSA-NCAM probably by direct interaction with neurons and glia.